Peningkatan Kapasitas Tempat Penampungan Sementara (TPS) Ciroyom Menjadi Stasiun Peralihan Antara (SPA) Berskala Kawasan di Kecamatan Andir, Kota Bandung - I Made Wahyu Widyarsana; Oloan Ivan Daniel (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
Ciroyom TPS is one of the waste facilities in Andir Sub-district. Ciroyom TPS is managed by PD Kebersihan Kota Bandung which works as temporary solid waste collection from residential and Ciroyom Market. The large area of the TPS Ciroyom service area, which is 5 out of 6 villages that produce large amounts of waste that reaches 45.43 tonnes/day. It makes the amount of waste transportation from TPS to TPA reach 12 ritation/day. The distance from TPS (Tempat Penampungan Sementara) Ciroyom to Sarimukti Regional Landfill which requires 44 km is a major consideration needed by the Waste Transfer Station (SPA, Stasiun Peralihan Antara) for regional scale. SPA takes in reducing the volume of waste so that it can reduce the ratio of garbage transportation to landfill (TPA, Tempat Pemrosesan Akhir). With adequate land area, TPS Ciroyom has the potential to improve its function to become a SPA for regional scale. Through the analysis of several alternative concepts and development scenarios, the amount of waste generated will be managed at the SPA Ciroyom for the next 10 years. The main facilities designed at the SPA Ciroyom for regional scale are waste compaction units resulting in volume reduction with the vertical compression method. Through solidification of waste, residual waste classified as residues is expected to reduce the volume by 60-70%. In addition, other facilities are provided which are designed at Ciroyom Area Scale SPA such as waste sorting facilities using conveyor belts, organic waste processing with open windrow systems, and inorganic waste recovery facilities that still have selling points.